Konsekwencje przyjęcia przez Polskę wspólnotowych instrumentów polityki handlowej Unii Europejskiej - Rudnicka, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
After Poland's accession to the European Union, the new common law concerning the rules, mechanisms and instruments of foreign trade policy was implemented. Recognition and adaptation to the EU requirements is a challenge not only for Polish enterprises but also for the administration. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 276-285